Carcass characterization of the slaughtered sheep in a meat processing plant in Córdoba, Colombia - Aguayo-Ulloa, Lorena Angélica (2021)
Introduction. In Colombia, sheep are a promising species for meat production; however, reports on the characteristics of the carcass at a commercial level in the region are unknown. Objective. To diagnose the carcass quality of the sheep slaughtered in a meat processing plant in the Department of Cordoba, Colombia. Materials and methods. From May 2017 to July 2018, variables were recorded in 883 sheep (phenotype, live weight, and sex) and their carcasses (weights, conformation and fatness, intrathoracic hemorrhages, morphometry, and pH at 24 h). A sampling was carried out on four groups of carcasses from castrated (C) and whole (E) animals, with three slaughter weights (lights: CL=±23.8 kg and EL= 23.9 kg; medium: CM=±27.7 kg; heavy: EP=36.2 kg) in an unbalanced design, to evaluate carcass and tissue composition of the shoulder. Results. The hot carcass weight (PCC), carcass yield (RCC), and compactness index were 11.11 kg; 41.49 %, and 0.19. The carcasses showed normal to poor muscular conformation (87.7 %) and very low-fat cover (68.7 %). Males accounted for 84.3 % of the carcasses, with a PCC of 10.86±0.09 kg and a RCC of 41.51±0.1 %. Females, mostly older than one year (66.90 %), had significantly higher PCC 12.47±0.22 kg, but similar RCC than males. Intrathoracic hemorrhages occurred in 10.9% of the carcasses; pH24 in males and females were 5.84±0.01 and 5.94±0.03, respectively. The CL, CM, EL, and EP of carcasses presented, respectively, 63.66, 61.74, 62.17, and 64.80 % of muscle (p<0.05), 7.20, 11.56, 6.48, and 6.80 % of total fat (p<0.001), and 21.35, 19.66, 23.45, and 21.07 % of bone (p<0.001). Conclusion. The sheep presented low slaughter weight, with heterogeneous carcasses, with normal to poor muscular conformation, low compactness index, and very lean.